Somatic characteristics of health children with hearing deprivation - Svitlana Savlyuk; Iryna Khmelnytska (Kazimierz Wielki University, 2017)
Abstract. Objective: to determine the level of somatic health of primary school children with hearing deprivation (HD) of special boarding school. The study involved 139 students 6-10 years with hearing deprivation. Results: it was found that boys and girls 6-10 years with HD scored from 3 to 5 points that determines the level of their physical health as below average physical health level. Boys and girls 6-10 years scored 5 points and were classified respectively to groups I health group - children with low health level: sick children with chronic illness and poor physical health. Conclusions. According to the analysis of medical records and interviews with school medical staff and parents, 100% of children we surveyed had low physical health scores, except Robinson's index, and were assigned to the I health group, which indicates a low somatic health level and poorly adaptation to the new training and education conditions. These are children who require more careful attention of doctors and teachers of special boarding school.